Leucaena sp recombinant cinnamyl alcohol dehydrogenase: purification and physicochemical characterization - Patel, Parth; Gupta, Neha; Gaikwad, Sushama M.; Agrawal, Dinesh C.; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2014)
Cinnamyl alcohol dehydrogenase is a broad substrate specificity enzyme catalyzing the final step in monolignol biosynthesis, leading to lignin formation in plants. Here, we report characterization of a recombinant CAD homologue (LICAD2) isolated from Leucaena leucocephala. LICAD2 is 80 kDa homodimer associated with non-covalent interactions, having substrate preference toward sinapaldehyde with K-cat/K-m of 11.6 x 10(6) (M-1 s(-1)), and a possible involvement of histidine at the active site. The enzyme remains stable up to 40 C, with the deactivation rate constant (K-d*) and half-life (t(1/2)) of 0.002 and 5 h, respectively. LICAD2 showed optimal activity at pH 6.5 and 9 for reduction and oxidation reactions, respectively, and was stable between pH 7 and 9, with the deactivation rate constant (K-d*) and half-life (t(1/2)) of 7.5 x 10(-4) and 15 h, respectively. It is a Zn-metalloenzyme with 4 Zn2+ per dimer, however, was inhibited in presence of externally supplemented Zn2+ ions. The enzyme was resistant to osmolytes, reducing agents and non-ionic detergents. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cinnamyl alcohol dehydrogenase (CAD); Metalloenzyme; Substrate specificity

Bacopa monniera recombinant mevalonate diphosphate decarboxylase: biochemical characterization - Shakeel Abbassi; Vishwakarma, Rishi K.; Patel, Parth; Kumari, Uma; Khan, Bashir Mohammad (International Journal of Biological Macromolecules, 2015)
Mevalonate diphosphate decarboxylase (MDD; EC 4.1.1.33) is an important enzyme in the mevalonic acid pathway catalyzing the Mg2+-ATP dependant decarboxylation of mevalonate 5-diphosphate (MVAPP) to isopentenyl diphosphate (IPP). Bacopa monniera recombinant MDD (BmMDD) protein was overexpressed in Escherichia coli BL21 (DE3) strain and purified to apparent homogeneity. K-m and V-max for MVAPP were 144 mu M and 52 U mg(-1) respectively. The values of turnover (k(cat)) and k(cat)/K-m, for mevalonate 5-diphosphate were determined to be 40 s(-1) and 2.77 x 10(5) M-1 s(-1) and k(cat) and k(cat)/K-m values for ATP were found to be 30 s(-1) and 2.20 x 10(4) M-1 s(-1), respectively. pH activity profile indicated the involvement of carboxylate ion, lysine and arginine for the activity of enzyme. The apparent activation energy for the BmMDD catalyzed reaction was 12.7 kJ mol(-1). Optimum pH and temperature for the forward reaction was found to be 8.0 and 45 degrees C. The enzyme was most stable at pH 7 at 20 degrees C with the deactivation rate constant (K-d(*)) of 1.69 x 10(-4) and half life (t(1/2)) of 68 h. The cation studies suggested that BmMDD is a cation dependant enzyme and optimum activity was achieved in the presence of Mg2+. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Mevalonate diphosphate decarboxylase; pH activity profile; Phylogenetic analysis; stability

Overexpression of squalene synthase in withania somnifera leads to enhanced withanolide biosynthesis - Patel, Neha; Patel, Parth; Kendurkar, Shuchishweta V.; Thulasiram, Hirekodathakallu V.; Khan, Bashir Mohammad (Plant Cell Tissue and Organ Culture, 2015)
Genetic engineering of secondary metabolic pathways is an emerging area of research for production and improvement of natural products in plant biotechnology. Here, we describe a systematic approach to manipulate a key regulatory step of isoprenoid biosynthetic pathway in Withania somnifera to study its effect on withanolide production. We generated T-0 W. somnifera plants overexpressing squalene synthase (WsSQS) by Agrobacterium tumefaciens mediated transformation, which were analyzed by Gus biochemical assay and PCR of hygromycin phosphotransferase (hptII) and WsSQS. qRT-PCR analyses of various transformed tissues indicated 2-5 fold increase in WsSQS transcripts in both T-0 and T-1 generations. The tissue specific protein expression studies revealed 2-3 fold increase in WsSQS, which was further confirmed by enzyme activity. These observations were corroborated with the 1.5-2 fold increase in total withanolide content of the transformed tissues. However, in leaf tissue, the levels of Withaferin A and Withanolide A increased significantly up to 4-4.5 fold. These findings demonstrate genetic engineering of isoprenoid pathway in W. somnifera resulting in enhanced production of withanolides, and also provide insights into such metabolic pathways for their manipulation to improve the pharmacological content of different medicinally important plants.
Keywords: Agrobacterium tumefaciens; Solanaceae; Squalene synthase; Withania somnifera; Withanolides